Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2005
DOI: 10.1145/1054972.1055094
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of end-user debugging software features

Abstract: Although gender differences in a technological world are receiving significant research attention, much of the research and practice has aimed at how society and education can impact the successes and retention of female computer science professionals-but the possibility of gender issues within software has received almost no attention. If gender issues exist with some types of software features, it is possible that accommodating them by changing these features can increase effectiveness, but only if we know w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 37 publications
(59 reference statements)
6
43
1
Order By: Relevance
“…Females came into the study with lower self-efficacy (measured via a self-efficacy question set [Compeau and Higgins 1995]) than males, scoring an average of 38 out of a possible 50, compared to 42 for males (Wilcoxon Rank-Sum Test: Z = -2.64, p < .01). This is consistent with similar self-efficacy differences for end users engaging in other complex computer tasks [Beckwith et al 2005, Subrahmaniyan et al 2008]. As we show in the next section, our results about differences in barriers are consistent with prior research in another aspect as well: these prior works showed gender differences in both features used and the strategies end users employed to find and fix errors in spreadsheets.…”
Section: Gender Differences In Barrier Encounters **D1supporting
confidence: 91%
See 1 more Smart Citation
“…Females came into the study with lower self-efficacy (measured via a self-efficacy question set [Compeau and Higgins 1995]) than males, scoring an average of 38 out of a possible 50, compared to 42 for males (Wilcoxon Rank-Sum Test: Z = -2.64, p < .01). This is consistent with similar self-efficacy differences for end users engaging in other complex computer tasks [Beckwith et al 2005, Subrahmaniyan et al 2008]. As we show in the next section, our results about differences in barriers are consistent with prior research in another aspect as well: these prior works showed gender differences in both features used and the strategies end users employed to find and fix errors in spreadsheets.…”
Section: Gender Differences In Barrier Encounters **D1supporting
confidence: 91%
“…Although our data are sparse, our female participants tended to have more questions about UI features than male participants ( research [Beckwith et al 2005] has investigated gender differences in the adoption of debugging features for traditional programs. In that work, females were hesitant about adopting new features; they adopted them less frequently and later in the process than familiar features, and this had repercussion on new bugs introduced through their debugging activities.…”
Section: Gender Differences In Information Needs **D1mentioning
confidence: 99%
“…The system used in the study will be Forms/3 with WYSIWYT [2]. Initially a think-aloud study will be carried out.…”
Section: Designmentioning
confidence: 99%
“…Verbalizations and end users' interaction with the application will be recorded for qualitative analysis, similar to procedures done in [3]. If cultural differences appear in feature acceptance and use, a large quantitative study will be carried out to confirm the results [2].…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation